Analysis of the labor conflict level and employees behave in conflict situations - Volodchenkova, Daryna; Volodchenkova, Natalia (My University, 2019)
The data of the result of research of the factors that cause the occurrence of labor disputes (conflicts) in the company are presented in the work. Improvement of the classification of objective and subjective reasons for the emergence of elective labor disputes (conflicts) will enable employees of the company to choose proper methods for managing conflict situations, which are characterized by the above types of objective and subjective reasons.
Keywords: кафедра екології та екоменеджменту; conflicts; labor disputes; factors; company; конфлікти; трудові спори; фактори; компанія